A study on clinico-histopathological patterns of ovarian tumors - Wills, Vinitha; Mathew, Rachel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ovarian tumors are an increasing cause for morbidity and mortality world over. The objective of this study was to study the distribution of ovarian tumors histopathologically in different age groups and their various clinical presentations. Methods: Ninety eight patients who presented with 140 ovarian lesions on either or both sides were analyzed during a study period of one year and a further one year follow-up of patients with malignant tumors were done in a Tertiary teaching hospital. Results: There were 140 lesions comprising of 40% of neoplastic lesions and 60% of non-neoplastic lesions. Among the ovarian neoplasms, 91.1% were benign lesions, 7.1% malignant and 1.8% were borderline malignant. Serous tumors were the commonest tumors (46.4%) followed by mucinous tumors and germ cell tumors (23.2% each). Endometriotic cysts (34.5%) were the commonest non-neoplastic lesions. The distribution of benign tumors in the reproductive age groups was only slightly more than that in the perimenopausal age group. All malignant tumors were in the perimenopausal age group. Menstrual complaints like irregular bleeding and menorrhagia formed the majority of clinical presentation. Bilaterality of lesions was seen in 16 patients. Conclusions: Benign ovarian tumors are common in reproductive age group as well as perimenopausal age group. The most common neoplasm present was surface epithelial tumors - serous tumors followed by germ cell and mucinous tumors. The most common non-neoplastic lesions were endometriotic cysts and inclusion cysts. Bilateral involvement was uncommon with preponderance of lesions on the right side. Common clinical presentations were menstrual problems and abdominal pain.